2011
DOI: 10.1098/rsbl.2011.0286
|View full text |Cite
|
Sign up to set email alerts
|

Tactic-dependent plasticity in ejaculate traits in the swordtail Xiphophorus nigrensis

Abstract: In species with alternative reproductive tactics, males that sneak copulations often have larger, higher quality ejaculates relative to males that defend females or nest sites. Ejaculate traits can, however, exhibit substantial phenotypic plasticity depending on a male's mating role in sperm competition, which may depend on the tactic of his competitor. We tested whether exposure to males of different tactics affected sperm number and quality in the swordtail Xipophorus nigrensis , a sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(22 citation statements)
references
References 28 publications
0
22
0
Order By: Relevance
“…For example, in the Arctic charr, Salvelinus alpinus, and fowl, Gallus gallus (Rudolfsen et al 2006, Cornwallis & Birkhead 2007, changes in social status resulted in changes in sperm velocity, with socially dominant males, who experience reduced levels of sperm competition, producing ejaculates in which sperm have reduced swimming speeds compared with socially subordinate males. In the swordtail Xiphophorus nigrensis, a species with alternative reproductive tactics, small sneaker males increased their sperm swimming speed when paired with other sneaker males (Smith & Ryan 2011). These changes in sperm velocity occurred rapidly: over 3 days in Arctic charr, 7 days in X. nigrensis, and 2 weeks in fowl.…”
Section: Evolution Of Sperm Size and Speedmentioning
confidence: 94%
See 1 more Smart Citation
“…For example, in the Arctic charr, Salvelinus alpinus, and fowl, Gallus gallus (Rudolfsen et al 2006, Cornwallis & Birkhead 2007, changes in social status resulted in changes in sperm velocity, with socially dominant males, who experience reduced levels of sperm competition, producing ejaculates in which sperm have reduced swimming speeds compared with socially subordinate males. In the swordtail Xiphophorus nigrensis, a species with alternative reproductive tactics, small sneaker males increased their sperm swimming speed when paired with other sneaker males (Smith & Ryan 2011). These changes in sperm velocity occurred rapidly: over 3 days in Arctic charr, 7 days in X. nigrensis, and 2 weeks in fowl.…”
Section: Evolution Of Sperm Size and Speedmentioning
confidence: 94%
“…In these insects, males appear able to detect not just the mating status of a female, be she mated or unmated, but also the number of males she has accepted, based on chemical cues left by males during copulation. Thus, when the perceived risk of sperm competition is elevated, males will produce ejaculates containing sperm of higher viability, but as the number of males competing for fertilizations is increased beyond two males, so that the payoff from a given male's investment in his ejaculate declines, males produce ejaculates containing sperm of decreasing viability , Thomas & Simmons 2007 (Smith & Ryan 2011) point to strategic adjustments in sperm quality with risk of sperm competition; in these cases, males ejaculate sperm with faster swimming speeds when they perceive a threat from rival males, or with females of greater reproductive value. However, these studies beg the question of how males adjust the quality of their sperm?…”
Section: Strategic Adjustments In Seminal Fluid Compositionmentioning
confidence: 99%
“…Specifically, males should increase their ejaculate expenditure when faced with a risk of sperm competition from rival males, but reduce their expenditure as the number of males competing for a given set of ova increases (sperm competition intensity), because the fitness pay-off per unit of ejaculate expenditure is expected to decline as the number of males competing increases [38]. Studies of mammals [172,173], fish [174,175], birds [176] and insects [177] have all reported increased numbers of sperm ejaculated when males perceive cues to the presence of rival males (sperm competition risk). Indeed, two recent meta-analyses of the literature have reported moderate sized and general effects of the presence of rivals on ejaculate expenditure [178,179].…”
Section: Post-copulatory Sexual Selection Acting On Malesmentioning
confidence: 99%
“…; Fitzpatrick et al. ), and that plastic responses to the social environment vary in these roles (Smith and Ryan ). Currently, data on strategic responses in sperm motility within mammal species are significantly limited.…”
mentioning
confidence: 99%